REMEDIASI MISKONSEPSI PESERTA DIDIK DENGAN FEEDBACK MENGGUNAKAN BROSUR PADA MATERI GERAK JATUH BEBAS DI SMA - Muharna, Rizka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aimed to know the effectiveness of feedback using brochures in remediating studentsâ€™ misconceptions about free fall motion in SMAN 1 Sungai Raya. This research was a quasy experimental design with nonequivalent control group design. The sample was the students of class X MIA 3 (N=23) as the experiment class 1 and X MIA 5 (N=25) as the experiment class 2 were chosen by intact group. The instrument of data collecting used diagnostic test like multiple choices with open reasons. The results showed that the percentage of students who misconception were 85.98% and 89.33% at pretest. There were declines in the number of students who misconception about 70.33% and 44.1%. Based on the Mann-Whitney U test, there was the significant difference of the number of studentsâ€™ misconceptions between the class remediated with feedback using brochures and without brochures (ð‘ð‘ ð‘ð‘œð‘Ÿð‘’= -2.41; ð›¼= 5%). The effectiveness of feedback using brochures in remediating studentsâ€™ misconceptions to decrease the number of students who misconception is medium (d = 0.66). This research is expected to alternative inÂ remediating studentsâ€™ misconceptions especially in physics.Â Keywords: Remediation, Misconception, Feedback, Brochures, Free Fall MotionÂ